Glycoside hydrolase subfamily GH5_57 features a highly redesigned catalytic interface to process complex hetero‐β‐mannans. Issue 11 (27th October 2022) - Martins, Marcele P.; Morais, Mariana A. B.; Persinoti, Gabriela F.; Galinari, Rafael H.; Yu, Li; Yoshimi, Yoshihisa; Passos Nunes, Fernanda B.; Lima, Tatiani B.; Barbieri, Shayla F.; Silveira, Joana L. M.; Lombard, Vincent; Terrapon, Nicolas; et al.
Abstract : A phylogenetically distant glycoside hydrolase family 5 member retrieved from the capybara gut microbiome displays a large and open catalytic interface that is adapted to recognize complex heteromannans, establishing the novel GH5_57 subfamily. This study expands the current mechanistic and functional understanding of one of the largest GH families. Abstract : Glycoside hydrolase family 5 (GH5) harbors diverse substrate specificities and modes of action, exhibiting notable molecular adaptations to cope with the stereochemical complexity imposed by glycosides and carbohydrates such as cellulose, xyloglucan, mixed‐linkage β‐glucan, laminarin, (hetero)xylan, (hetero)mannan, galactan, chitosan, N‐glycan, rutin and hesperidin. GH5 has been divided into subfamilies, many with higher functional specificity, several of which have not been characterized to date and some that have yet to be discovered with the exploration of sequence/taxonomic diversity. In this work, the current GH5 subfamily inventory is expanded with the discovery of the GH5_57 subfamily by describing an endo‐β‐mannanase (CapGH5_57) from an uncultured Bacteroidales bacterium recovered from the capybara gut microbiota. Biochemical characterization showed that CapGH5_57 is active on glucomannan, releasing oligosaccharides with a degree of polymerization from 2 to 6, indicating it to be an endo‐β‐mannanase. The crystal structure, which was solved using single‐wavelength anomalous diffraction, revealed a massively redesigned catalytic interface compared with GH5 mannanases. The typical aromatic platforms and the characteristic α‐helix‐containing β6–α6 loop in the positive‐subsite region of GH5_7 mannanases are absent in CapGH5_57, generating a large and open catalytic interface that might favor the binding of branched substrates. Supporting this, CapGH5_57 contains a tryptophan residue adjacent and perpendicular to the cleavage site, indicative of an anchoring site for a substrate with a substitution at the −1 glycosyl moiety. Taken together, these results suggest that despite presenting endo activity on glucomannan, CapGH5_57 may have a new type of substituted heteromannan as its natural substrate. This work demonstrates the still great potential for discoveries regarding the mechanistic and functional diversity of this large and polyspecific GH family by unveiling a novel catalytic interface sculpted to recognize complex heteromannans, which led to the establishment of the GH5_57 subfamily.